83.0k views
17 votes
What is the answer to this and please show how to solve it

What is the answer to this and please show how to solve it-example-1
User Catheline
by
4.8k points

1 Answer

3 votes

Explanation:


( \frac{ {18}^{ (1)/(4) } }{ {9}^{ (1)/(4) } } )^(3) \\ = \frac{1}{ (\frac{ {18}^{ (1)/(4) } }{ {9}^{ (1)/(4) } })^(3) } \\ = \frac{1}{ \frac{18^{ (3)/(4) } }{ {9}^{ (3)/(4) } } } \\ = \frac{ {9}^{ (3)/(4) } }{18^{ (3)/(4) } } \\ = \frac{ \sqrt[4]{ {9}^(3) } }{ \sqrt[4]{ {18}^(3) } } \\ = \frac{ \sqrt[4]{729} }{ \sqrt[4]{5832} } \\ = 0.5946

User Ishan Shah
by
5.2k points